2003
DOI: 10.1046/j.1365-2249.2003.02180.x
|View full text |Cite
|
Sign up to set email alerts
|

Beta-2-glycoprotein I expression on monocytes is increased in anti-phospholipid antibody syndrome and correlates with tissue factor expression

Abstract: SUMMARYIt is well known that monocytes may play an active role in thrombogenesis, since they may express on their surface tissue factor, the major initiator of the clotting cascade. The results of this investigation demonstrate beta-2-glycoprotein I ( b 2 -GPI) mRNA expression by human peripheral blood monocytes, indicating that these cells synthesize b 2 -GPI. In addition, we show b 2 -GPI expression on cell surface of these cells by flow cytometric analysis, and the presence of this protein in cell lysate by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
22
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 26 publications
(38 reference statements)
8
22
0
2
Order By: Relevance
“…More recently apoH mRNA was found by RT-PCR on RNA extracted from other tissues (intestine, placenta, foetal astrocytes, lymphocytes) or cultured cells (transformed cell lines) such as choriocarcinoma, hepatoma (36), colon adenocarcinoma (35), neuroblastoma, umbilical vein endothelial cells (HUVEC, but not for Alvarado-de la Barrera, 39), astrocytoma, glioblastoma cells (40) and in monocytes (41).…”
Section: Introductionmentioning
confidence: 99%
“…More recently apoH mRNA was found by RT-PCR on RNA extracted from other tissues (intestine, placenta, foetal astrocytes, lymphocytes) or cultured cells (transformed cell lines) such as choriocarcinoma, hepatoma (36), colon adenocarcinoma (35), neuroblastoma, umbilical vein endothelial cells (HUVEC, but not for Alvarado-de la Barrera, 39), astrocytoma, glioblastoma cells (40) and in monocytes (41).…”
Section: Introductionmentioning
confidence: 99%
“…The best described antigen in APS is β-2 glycoprotein I (β 2 GPI). β 2 GPI, a cationic lipid-binding protein with unclear function, is made especially by the liver and circulates at high levels in plasma (50-200 μg/ml) (6,7). It has been suggested that anti-β 2 GPI antibodies potentiate thrombosis by engaging β 2 GPI on cell surfaces, thereby promoting cell activation (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Furthermore, APLAs activate monocytes and platelets, the latter in the presence of subactivating doses of thrombin. [9][10][11][12] The activation of these cells leads to inflammatory and procoagulant responses that may underlie the hypercoagulable state that characterizes APS. 13,14 The mechanisms of cell activation by APLAs are still incompletely understood.…”
mentioning
confidence: 99%